A trama que sustentava o Império : mediação entre as elites locais e o Estado Imperial Brasileiro (Jaguarão, segunda metade do século XIX) - Both, Amanda Chiamenti (2016)
This master thesis analyzes the ways of articulation between the elite of a city and the Imperial State, through the acting of some individuals who mediated the interactions between this parts. Therefore, we elected as scenario the city of Jaguarão, that is located in the southwest border of the state of Rio Grande do Sul, because there were born Henrique d’Ávila and Jose Diana, two politicians that have threshed successful careers along the second half of XIX century, but they remained linked to the place they were born. Firstly we proceed to a characterization of the local elite which we were dealing it, what revealed traces of a closed and conservative elite. On the other hand, researching the trajectory of these individuals that performed the role of mediators, we found that they and their families were deeply intertwined with the elite of the city, what is, incluiding, one of the factors that enabled they to acting as mediators between the locality and the external world. However, a number of elements determines the ability of mediation of this individuals, as the relations they keep inside and, specially, out of the locality, of the positions they occupied and the prestigie that they had in a specific moment. Therefore, with variable efficiency according the listed conditions, the elite of Jaguarão had their interests represented in the government, indicating the active role of the local elites in the process of construction and maintenance of the Imperial State.